IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT BY USING REALIA MEDIA - Aris Girsang; Nitha F. V Liando; Mister G. Maru (Universitas Negeri Manado, 2020)
The aim of this research was to investigate whether the use of realia is effective in improving tenth grades ability in writing descriptive text or not. The research conducted at SMA Negeri 1 Tompaso, North Sulawesi, Indonesia, in which X MIPA 1 was chosen as the sample. This class consists of twenty-nine students. This quantitative research used a pre-experimental design with one group pre-test and post-test design. Pre-test has given before the treatment. After the writer gave a treatment, the writer collected the data for post-test. The result of this research showed that the mean score of pre-test is 4.86 and post-test is 7.48. This means that the result of post-test is higher than pre-test. In other words, this result may lead to conclusion that using realia media was considered to improve students’ ability writing descriptive